Implicações jurídicas na utilização de organismos geneticamente modificados: os alimentos transgênicos - Mello, Cecy Pereira Figueira da Silva Neta (2016)
With the biotechnology advancement and development, with special focus on genetic engineering, also rises the requirement of ethical fundamentals in a scenario of constant modifications. When it comes to transgenic food, there‟s controversy in the philosophical, ethical, environmental, political, legal and economic field because it‟s a subject which is inside of the daily reality, with very fast changes and in that context, the Brazilian and international legislation seems to doesn‟t follow the technology velocity and Science becomes a political and economical instrument. In this article, international law and national law related to the using of genetically modified organism are analyzed, pointing out the 11.105/05 law, considering the origin, shape and evolution of genetically modified organism, the importance of obeying the environmental law when handling and distributing products resulting of these genetic modifications to the public consumption, this law analysis, going through the environmental impacts, giving importance to the cost-benefit and the risk expressly taken by the scientific community, besides the own concept of consumer, proving the need of genetically modified food labelling and the reality of what really happens in the process of patenting acquisition in the international law and in the Brazilian law and jurisprudence decisions.